No Plaything: Ethical Issues Concerning Child-pornography - King, Peter J. (2008)
Academic discussion of pornography is generally restricted to issues arising from the depiction of adults. I argue that child-pornography is a more complex matter, and that generally accepted moral judgements concerning pornography in general have to be revised when children are involved. I look at the question of harm to the children involved, the consumers, and society in general, at the question of blame, and at the possibility of a morally acceptable form of child-pornography. My approach involves an objectivist meta-ethics and a utilitarian view of practical ethics, and I bring out the advantages of these theories to the consideration of moral issues such as this one.
Keywords: Utilitarianism; Pornography; Objectivism; Mill; Ethics; Children